Relearning the calculus, connecting it to real-life - Mela Aziza (Universitas Pendidikan Ganesha, 2020)
Developing students’ abilities in solving real-life problems is one of the mathematics curriculum goals. Students may be motivated and interested as well as have good perceptions in learning mathematics when knowing the usefulness of mathematics for their life. However, teachers may have difficulties to connect some mathematics topics including calculus to students’ rela-life because of the nature of topic. Therefore, teachers have to know the teaching methods in teaching calculus and then connecting it to students’ life. Although, teachers will find some obstacles when teaching and connecting calculus to students’ real life, they may start to give more calculus problems to students. They also can use mathematics softwares to give sense of the usefulness of calculus in students’ life.